Dying for Data. - Charette, R.N.
With the support of and some funding from the federal government, a private-sector effort is underway to develop a comprehensive system of electronic health records linking hospitals, general practitioners, specialists, insurance offices and others across the US. Called the National Health Information Network, the project aims to replace paper-based files with digital record containing a patient's complete medical history, which can be accessed by health providers instantaneously wherever treatment is needed. It will consist not of one centralized system but of a large number of independently managed regional networks, somewhat comparable to the Internet itself. This paper looks at the recent history and some smaller-scale efforts to digitize medical records
Keywords: Internet; NHIN; National Health Information Network; Digitized medical records; Electronic health records; Health providers; Medical history